Impact of patency of the carotid terminus and middle cerebral artery on early clinical outcomes in patients with acute internal carotid artery occlusion and mild symptoms - Ryo Itabashi; Takuya Saito; Yuichi Kawabata; Yuya Kobayashi; Yukako Yazawa (Cerebrovascular Diseases Extra, 2022)
Introduction: Both collateral flow via the internal carotid artery (ICA) terminus (ICT) and initial mild symptoms might be associated with favorable outcomes in patients with acute ICA occlusion (ICAO). This study aimed to address the association between early clinical outcomes and patency of the ICT and middle cerebral artery (MCA) in patients with acute ICAO with mild symptoms. Methods: Of 1214 consecutive patients with acute ischemic stroke or transient ischemic attack due to large vessel occlusion, patients with ipsilateral ICAO and initial National Institutes of Health Stroke Scale score (NIHSS) ≤ 5 were retrospectively enrolled. We examined the associations between clinical factors including patency of the ICT and MCA and recurrence of stroke or early neurological deterioration (REND). Significant early neurological deterioration was defined as increment in NIHSS score ≥ 1 during hospital stay. Results: Thirteen of the 35 patients who were finally enrolled had REND (37%), and median modified Rankin Scale (mRS) score at discharge was 1 (interquartile range, 0–4). Initial NIHSS score (4 vs. 1, p<0.001) and rates of diabetes mellitus (61.5% vs. 13.6%, p=0.007), intravenous thrombolysis (IVT) (30.9% vs. 0%, p=0.014), and mechanical thrombectomy (MT) (23.1% vs. 0%, p=0.044) were significantly higher in patients with REND rather than in those without. The rate of patent ICT and MCA was comparable between groups. Except for one patient who underwent MT promptly after IVT immediately after REND, 3 patients initially treated with IVT deteriorated after the procedure. One patient without patent ICT and MCA did not meet the indications for MT. In 2 other patients with patent ICT and MCA, MT was not initially performed, but was eventually performed because of REND due to thrombus migration, and both were discharged with an mRS score of 5. Conclusion: The overall clinical outcomes of patients with acute ICAO with mild symptoms were not depending on the patency of the ICT and MCA, but initial treatment with IVT alone might risk unfavorable outcomes due to thrombus migration in patients with patent ICT and MCA.